The Influence of Empowering Leadership and Organizational Culture on Job Satisfaction and Performance of Renmin Personnel at the Ditsamapta of the North Maluku Regional Police - Elis Rahayu Putri Elis Rahayu Putri; Edi Jusriadi; Dg. Maklassa (LP2M IAIN Palopo, 2026)
This study aims to determine and analyze the effect of empowering leadership and organizational culture on job satisfaction and personnel performance at Renmin Ditsamapta of North Maluku Regional Police. This research is a quantitative study usi ng questionnaires as data collection instruments. The research respondents consisted of 32 personnel from the Renmin Division of Ditsamapta at the North Maluku Regional Police. The data analysis technique used to examine the influence between variables was Structural Equation Modeling (SEM). The data analysis technique used to examine the effect between variables is Structural Equation Modeling (SEM). The results show that empowering leadership and organizational culture have a positive and significant effect on job satisfaction and personnel performance. Job satisfaction also has a positive and significant effect on personnel performance and is able to mediate the effect of empowering leadership and organizational culture on personnel performance.